Wayfinding Problems for Blind Pedestrians at Noncorner Crosswalks: Novel Solution. Issue 1 (2017) - Bentzen, Billie Louise (Beezy); Barlow, Janet M.; Scott, Alan C.; Guth, David; Long, Richard; Graham, Jennifer
To travel independently, pedestrians with visual impairments must be able to locate crosswalks and align accurately for crossing streets. This action is especially challenging where crossings are not located at street corners and cues for locating the crosswalk and aligning to cross in the direction of travel on the crosswalk may be inadequate. This research compared midblock and roundabout crossings with curb ramps and detectable warnings but no other consistent cues for locating the crosswalk and no cues specifically intended to provide alignment and heading information, with the same crossings with the addition of a 24-in.-wide prototype surface of raised bars oriented perpendicular to the direction of travel on the crosswalks. This treatment was installed beside the detectable warnings and extended across the sidewalk. It was hypothesized that this surface would assist with both locating the crosswalk and establishing accurate alignment with the crosswalk. Sixteen participants having little or no vision failed, on average, to locate the crosswalk on the initial approach on 2.4% of their attempts for crosswalks having the guidance surface, while without the guidance surface, participants failed to locate the crosswalk on the initial approach on an average of 17.9% of their crossing attempts. With the guidance surface, participants aligned correctly on average on 77.3% of their trials, while without the surface the rate of correct alignment was 52.1%.